Breastfeeding and Postnatal Depression: A Prospective Cohort Study in Sabah, Malaysia - Mohamad Yusuff, Azi; Tang, Li; Binns, Colin; Lee, Andy (2015)
BACKGROUND: Postnatal depression is a disorder that can lead to serious consequences for both the mother and infant. Despite the extensively documented health benefits of breastfeeding, its association with postnatal depression remains uncertain. OBJECTIVE: To investigate the relationship between full breastfeeding at 3 months postpartum and postnatal depressive symptoms among mothers in Sabah, Malaysia. METHODS: A prospective cohort study of 2072 women was conducted in Sabah during 2009-2010. Participants were recruited at 36 to 38 weeks of gestation and followed up at 1 and 3 months postpartum. Depressive symptoms were assessed using the validated Malay version of the Edinburgh Postnatal Depression Scale (EPDS). Repeated-measures analyses of variance was performed to compare the depression scores over time and between subgroups of breastfeeding mothers. RESULTS: Approximately 46% of women were fully breastfeeding their infants at 3 months postpartum. These mothers had significantly (P < .001) lower mean EPDS scores at both 1 and 3 months postpartum (mean ± SD, 4.14 ± 4.12 and 4.27 ± 4.12, respectively) than others who did not initiate or maintain full breastfeeding for 3 months (4.94 ± 4.34 and 5.25 ± 4.05, respectively). After controlling for the effects of covariates, the differences in EPDS scores remained statistically significant (P = .001) between the 2 breastfeeding groups. CONCLUSION: Full breastfeeding appeared to be negatively associated with postnatal depressive symptoms for mothers residing in Sabah.